Fibrinogen adsorption study on ultrananocrystalline diamond as a biocompatible and antithrombogenic interfacial material for implantable devices. Issue 12 (11th September 2014) - Zeng, Hongjun; Arumugam, Prabhu U.; Carlisle, John A.
<x xml:space="preserve">Abstract</x> In this work, we have demonstrated that ultrananocrystalline diamond (UNCD®) film, has significantly lower fibrinogen adsorption than the conventional implantable materials and other diamond types, nanocrystalline or microcrystalline diamond films. In addition, we developed a hot hydrogen treatment in a hot filament chemical vapor deposition (CVD) system, to realize a hydrogen terminated (H‐terminated) UNCD surface. The change in surface termination of H‐terminated surfaces was characterized by contact angle measurements. Fibrinogen adsorption studies were conducted on three different types of UNCD surfaces: as‐deposited, oxidized, and hydrogenated using florescence microscopy. The results reveal that H‐terminated UNCD surface has the lowest fibrinogen adsorption, which suggests an excellent biocompatibility and anti‐thrombogenicity. The authors have also studied the stability of the H‐termination UNCD surface in dynamic fibrinogen‐NaHCO3 solution for 2 weeks and in air for half year, no surface chemistry change was observed from both cases.